2012
DOI: 10.1016/j.eururo.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Trial of Sunitinib in Patients with Advanced Non–clear Cell Renal Cell Carcinoma

Abstract: Background Sunitinib is a standard of care treatment in advanced clear-cell renal cell carcinoma (ccRCC). Retrospective and expanded access data suggest sunitinib has activity in advanced non-clear cell RCC (nccRCC). Objective To prospectively determine the clinical efficacy and safety of sunitinib in patients with advanced nccRCC. Design, Setting, and Participants This is a single-arm phase 2 trial with a two-stage design. Eligibility criteria included pathologically confirmed nccRCC or ccRCC with ≥ 20 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 30 publications
(30 reference statements)
6
106
1
1
Order By: Relevance
“…The clinical study has been previously described [3]. The primary endpoints were the objective response rate and progression-free survival (PFS).The secondary endpoints were safety and overall survival (OS).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical study has been previously described [3]. The primary endpoints were the objective response rate and progression-free survival (PFS).The secondary endpoints were safety and overall survival (OS).…”
Section: Patientsmentioning
confidence: 99%
“…The disease characteristics have been previously summarized [3]. Of the 57 patients, 27 (47%) had papillary RCC (2 with type I, 11 with type II, and 14 not specified), 8 (14%) had an unclassified variant, 7 (12%) had sarcomatoid, 6 (11%) had collecting duct/ renal medullary, 5 (9%) had chromophobe, and 4 (7%) had other forms of nccRCC.…”
Section: Patient Outcomes and Disease Characteristicsmentioning
confidence: 99%
“…[160][161][162][163][164][165][166][167] A phase II trial of 31 patients with non-clear cell RCC treated with sunitinib reported an ORR of 36% (95% CI, 19%-52%) and median PFS of 6.4 months (95% CI, 4.2-8.6 months). 165 In another study of 53 patients with non-clear cell RCC (papillary or chromophobe), the ORR to sunitinib or sorafenib was 23%; median PFS was 10.6 months.…”
Section: Sunitinibmentioning
confidence: 99%
“…A. Bilen и соавт. представили результаты иссле-дования II фазы, в котором оценивали зависимость эффективности сунитиниба от развития гипертензии, а также циркулирующих цитокинов и ангиогенных факторов у больных нПКР [41,42]. Сунитиниб полу-чали 57 пациентов с папиллярным, хромофобным, медуллярным, неклассифицируемым ПКР и раком из собирательных трубочек.…”
Section: ингибиторы тирозинкиназыunclassified